Knowledge of undergraduate nursing students about human papillomavirus vaccine - Paula Hino; Nailde Cristina de Freitas; Priscilla Sete de Carvalho Onofre; Katia Lacerda de Souza; Jaqueline de Oliveira Santos (Rev Rene)
Objective: to identify the knowledge that undergraduate nursing students have about human papillomavirus vaccine. Methods: field research, descriptive, cross-sectional. Sample composed of 100 undergraduate nursing students of a private university, with use of a questionnaire. Data were analyzed using descriptive statistics. Results: among participants, 98.0% reported that they knew the human papillomavirus vaccine, 65.0% recognized the types of viruses against which the vaccine gives protection, and 51.0% had knowledge about the age group that is targeted to receive the vaccine in the public healthcare network. As for the features of the administration of the vaccine, such as dosage, route of administration, contraindications and adverse events, a level of knowledge below 60.0% was observed.Conclusion: insufficient knowledge on the human papillomavirus vaccine was found among the students participating in the present study and this stresses the need to give more attention to the discussion about the prevention of cervical cancer during the training of future nurses.